2013
DOI: 10.1242/dev.092569
|View full text |Cite
|
Sign up to set email alerts
|

Recombineering-based dissection of flanking and paralogous Hox gene functions in mouse reproductive tracts

Abstract: SUMMARYHox genes are key regulators of development. In mammals, the study of these genes is greatly confounded by their large number, overlapping functions and interspersed shared enhancers. Here, we describe the use of a novel recombineering strategy to introduce simultaneous frameshift mutations into the flanking Hoxa9, Hoxa10 and Hoxa11 genes, as well as their paralogs on the HoxD cluster. The resulting Hoxa9,10,11 mutant mice displayed dramatic synergistic homeotic transformations of the reproductive tract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 39 publications
1
54
0
Order By: Relevance
“…Hox genes have important roles in the development of organs that involve Hox expression along the anteriorposterior axis. Examples include the Hox3 paralogous group genes, which are crucial for thymus, thyroid and parathyroid development; Hox5 genes in lung development; Hox9, Hox10 and Hox11 genes in the reproductive tract; Hox10 and Hox11 genes in kidney development; and Hoxb13 for prostate development (Dolle et al, 1991;Benson et al, 1996;Gendron et al, 1997;Taylor et al, 1997;Manley and Capecchi, 1998;Podlasek et al, 1999;Economides and Capecchi, 2003;Schwab et al, 2006;Yallowitz et al, 2011;Boucherat et al, 2013;Raines et al, 2013;Hrycaj et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Hox genes have important roles in the development of organs that involve Hox expression along the anteriorposterior axis. Examples include the Hox3 paralogous group genes, which are crucial for thymus, thyroid and parathyroid development; Hox5 genes in lung development; Hox9, Hox10 and Hox11 genes in the reproductive tract; Hox10 and Hox11 genes in kidney development; and Hoxb13 for prostate development (Dolle et al, 1991;Benson et al, 1996;Gendron et al, 1997;Taylor et al, 1997;Manley and Capecchi, 1998;Podlasek et al, 1999;Economides and Capecchi, 2003;Schwab et al, 2006;Yallowitz et al, 2011;Boucherat et al, 2013;Raines et al, 2013;Hrycaj et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In a study, frameshift mutations were observed in the HOXA9, HOXA10 and HOXA11 genes in mice; and dramatic changes were occurred in the reproductive systems of both male and female mice. It was determined that these mutations led to developmental problems in the uterus and oviduct of female mice, and the vas deferens and epididymis of male mice . In the current study, the identification of Amp in patients 3, 13, 15, 21, 34, 37 and 38, and Del in patient 24 in the HOXD9 gene indicates that the Amp/Del changes in this gene might have a direct effect on the development of the male reproductive system.…”
Section: Discussionmentioning
confidence: 57%
“…The top 10 transcription factors enriched in these gene promoters included several known to be involved in regulatory programs in skeletal muscle or in vascular smooth muscle, including RP58, NF1, TAL1, NOTCH1, PAX4, cJUN, HOXA9, and MEIS1 ( Fig. 2A) (Kami et al, 1995;Tao et al, 1998;Knoepfler et al, 1999;Daury et al, 2001;Ema et al, 2003;Di Padova et al, 2007;Yokoyama et al, 2009;Kossler et al, 2011;Raines et al, 2013;Mourikis and Tajbakhsh, 2014;Summers et al, 2015). To narrow this putative regulator list to those potentially relevant to ICM regulation, we again turned to the in situ patterns.…”
Section: Identification Of Transcriptional Regulators Of Intestinal Vmentioning
confidence: 99%